Perception of the population of city of Santa Bárbara (MG) about the minerary activity and contamination of soil and water by arsenic (Research, Society and Development, 2017)
Mining, as well as various other economic activities, causes environmental problems. Thus, through questionnaires given to 380 respondents Santa Barbara (MG), we evaluated the perception of this population about mining and its impacts. As a result, 38% mentioned it as being a negative activity because of the environmental consequences for it triggered. On the other hand, 60% of respondents considered it as positive, highlighting the creation of jobs and the development of the municipality. Regarding the participants' knowledge of arsenic, 38.9% of respondents said they did not know and 39.5% said they know it. Worryingly, 87.9% of respondents said they ignore their toxicity.